(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Two-phase (nonporous) magnetic alkali borosilicate glasses have been produced by induction melting. Their macroscopic properties and crystal structure have been studied and it is shown that in the silica skeleton there are the agglomerates of Fe3O4. These agglomerates are formed by monodomain nanoparticles of magnetite and demonstrate the superparamagnetic properties. After special thermal treatment (liquation process) and chemical etching the nanoporous matrices with random dendrite pore structure and magnetic properties have been produced. The channels (porous space) were filled by ferroelectric materials KH2PO4 (KDP), KH2PO4+(NH4)H2PO4 (KDP-ADP or KADP), and NaNO2 and the effect of applied magnetic fields on phase transitions in these nanocomposite have been studied. It has also been established that a restricted geometry changed essentially the phase diagram of KADP.